Effects of the COVID-19 pandemic on the prevalence of obsessive-compulsive symptoms among young adults in Peru - Nicolas, Galdos Bejar Marcelo (2022)
The COVID-19 pandemic has exposed the general population to constant stressful and traumatic situations. This, added to the necessary and constant dissemination of preventive measures for COVID-19 infection, can generate an increase in the prevalence of Obsessive-Compulsive (OC) symptoms. Thus, this research aimed to evaluate the prevalence of OC symptoms and explore associated factors in young adults in Peru, the country with the highest COVID-19 death rate in the world. In this analytical cross-sectional study, an online survey distributed through social networks was used. OC symptomatology during the last week was measured by the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS). Possible Generalized Anxiety Disorder (GAD) and Major Depressive Disorder (MDD) were evaluated with the General Anxiety Disorder 7-items (GAD-7) and Patient Health Questionnaire-9 (PHQ-9), respectively. 1243 young adults were evaluated. Of these, the mean age was 24.1 years, 54.3% were women, and the prevalence of OC symptoms was 50%. Participants who had experienced a traumatic event during COVID-19 pandemic had higher prevalence of OC symptoms (PR 1.54; CI 95% 1.27 – 1.85), when compared to those did not experience such events. In the same way, participants diagnosed with depression (PR 2.37; CI 95% 1.96 – 2.86) and anxiety (PR 1.11; CI 95% 1.02 – 1.21) also had a higher prevalence of OC symptoms, compared with those without depression and anxiety. In conclusion, obsessive-compulsive symptomatology has a high prevalence in young adults, and is associated with the death of a family member or close friend from the COVID-19 disease. The prevalence of possible depression and anxiety are high and are associated with higher prevalence of obsessive-compulsive symptoms. This highlights the importance of including mental health programs during the pandemic for the population who has suffered traumatic events, to be able to give them adequate follow-up and support.